Factors Affecting SMEs' Intention to Adopt a Mobile Travel Application based on the Unified Theory of Acceptance and Use of Technology (UTAUT-2) - Kritcha Yawised; Darlin Apasrawirote; Maneerut Chatrangsan; Paisarn Muneesawang (Emerging Science Journal, 2020)
This study is part of a government research project which aims to synthesise the current evidence on the factors affecting the intention of mobile application adoption called ‘Tripper Notifier Application’ (TNA) for the hospitality and tourism industrial sector in Thailand. The focus is on small and medium enterprises (SMEs), which emphasize restaurants, hotels, and attraction sites. The present article examines various factors influencing the intention to use such applications by employing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) as the theoretical underpinning of this research paradigm. Using 84 selected research papers in Scopus published between 2020 and 2022, A thematic analysis incorporating a grounded theory approach to systematically generate themes was conducted, and the findings found three main themes, including business transformation capabilities (BTC), digital transformation capabilities (DTC), and personal innovativeness (PI), as an extension of UTAUT-2 as mediator and moderator variables. To this end, the study fills the research gaps and extends the UTAUT-2 framework by including an initiative of twelve inside attributes-based lines, including performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit behavior, behavioral intention, and use behavior, together with three moderators: age, gender, and experience. Finally, the context dimensions of the UTAUT-2 extensions were mapped to highlight all the constructs of the TNA adoption framework for future research directions. The novel contribution of this study is to fill the gap with both theoretical and practical knowledge. On the theoretical level, this study constitutes constructs based on UTAUT-2 theory as a research-based setting to fill a gap in research. On the practical level, it provides insights and information about new capabilities that SME owners, managers, and practitioners should consider in order to differentiate their own capabilities. Doi: 10.28991/esj-2021-SP1-014 Full Text: PDF